Introduction to Implementation Science for Research on Learning Disabilities. (November 2019) - Smolkowski, Keith; Crawford, Lindy; Seeley, John R.; Rochelle, Jonathan
In this overview of implementation science and implementation fidelity in the field of learning disabilities, authors provide a brief summary of current research related to implementation science followed by an introduction of the articles in this special series. Authors emphasize the relationship between the effectiveness of interventions and the difficulty of their implementation, highlighting the importance of considering both when adopting new interventions in the field of learning disabilities. The authors then turn their attention to the need for implementation science and implementation fidelity to be considered at all stages of research from program or intervention development to efficacy and effectiveness trials through large-scale implementation in real-world settings. An overview of active implementation frameworks as proposed by the National Implementation Research Network as well as a discussion on the importance of research–practice partnerships when implementing programs and interventions in the field of learning disabilities are also included.